1981
DOI: 10.1021/j150603a014
|View full text |Cite
|
Sign up to set email alerts
|

Reverse pulse voltammetry. Application to second-order following reactions

Abstract: 285seen in Figure 7, the presence of another factor is suggested to affect the reaction rates of the present oxidation. It is speculated that the most favorable steric conditions are met in the case of n = 1 for the attack of Ce(V). For example, the methyl group in AO+-CH3 may be directed toward the inside of surfactant layer. As a result, the carbon atom Cg, which is considered to be the site attacked by Ce(1V) ion, is exposed toward the water phase. On the other hand, the interaction of AOH+ with surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The electrochemical studies were carried out by conventional electrochemical methods, such as DC and normal-pulse polarography (NPP) and the recently introduced reverse-pulse polarographic (RPP) technique (29,30). RPP is a pulse-polarographic technique that has the quantitative merits of the double-potential-step method and the diagnostic strength of cyclic voltametry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical studies were carried out by conventional electrochemical methods, such as DC and normal-pulse polarography (NPP) and the recently introduced reverse-pulse polarographic (RPP) technique (29,30). RPP is a pulse-polarographic technique that has the quantitative merits of the double-potential-step method and the diagnostic strength of cyclic voltametry.…”
Section: Resultsmentioning
confidence: 99%
“…Products and intermediates are accumulated in the diffusion layer and their electroactivity is displayed during the application of a short anodic or cathodic potential pulse (milliseconds) during which the resulting current is measured. Examples of uses of RPP in electrode kinetics have been given elsewhere (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…However, measurements at a variety of drop times, r, and pulse widths, ip, showed that the height of this wave, írp,h2o2> 18 equal within experimental error to the height of the DC wave for reduction of H202. This indicates that this wave is due to oxidation of H202 diffusing to the electrode during the time of the pulse according to the equation H202 + 20H--02 + 2H20 + 2e" (3) It might be asked why, if this identification of the small wave is correct, this wave does not appear in the DC polarogram. The answer is quite simple.…”
Section: Resultsmentioning
confidence: 99%
“…Pulses are applied to successively more positive values, and the resulting curve of current vs. pulse potential is an RP polarogram of the product of the electrode reaction which takes place at the initial potential. Reverse pulse polarography has been used to study the mechanism of electrode reactions (2)(3)(4)(5)(6)(7)(8)(9), to determine diffusion coefficients (10), and for analytical purposes (11). The RP technique can be especially useful analytically when the voltammetric properties of the reaction product are more favorable than those of the reactant itself or when the reduction of the reactant is not well-separated from reduction waves for other substances in solution.…”
mentioning
confidence: 99%
“…Among other applications, this technique has been employed for evaluation of the electrochemical reversibility of electrode processes [3,4], in the study of electrogenerated products [3] and reaction mechanisms [5][6][7][8] and for determination of diffusion coefficients [9], being particularly valuable when unstable products are involved.…”
Section: Introductionmentioning
confidence: 99%